The Role of Influencer Marketing and Online Customer Review on Brand Attitude in Increasing Brand Loyalty, Brand Awareness, and Purchase Intention in Fashion Brands in Indonesia - Anugrah, Siska (Syntax Corporation, 2025)
This study aims to analyze the influence of influencer marketing on consumer attitudes (brand attitude), brand loyalty, brand awareness, and electronic Word of Mouth (eWOM) in driving purchase intentions in Indonesia’s fashion industry. Using a quantitative approach, data were collected from 300 respondents via online surveys and analyzed through Structural Equation Modeling (SEM). The findings reveal that influencer credibility, attractiveness, involvement, and influencer-brand congruence do not significantly affect brand attitude. However, online reviews and brand-consumer congruence enhance loyalty, brand awareness, and purchase intention. This study offers insights for fashion marketers in selecting suitable influencers and managing customer reviews effectively.